Factors Associated with Resilience of Adult Survivors Five Years after the 2008 Sichuan Earthquake in China - Ni, Cuiping; Chow, Meyrick Chum Ming; Jiang, Xiaolian; Li, Sijian; Pang, Samantha Mei Che (PLOS ONE, 2015)
Given the paucity of quantitative empirical research on survivors’ resilience and its predictors in the context of long-term recovery after disasters, we examined how resilience predictors differed by gender among adult survivors five years after the Sichuan earthquake. This was a cross-sectional survey study of adult survivors (N = 495; aged 18–60) living in reconstructed communities five years into the recovery process after the Wenchuan earthquake. The instruments we used included assessments of sociodemographic characteristics and earthquake exposure level, the Connor-Davidson Resilience Scale, and the Social Support Rating Scale. Support-seeking behaviors emerged as a significant predictor of male survivors’ resilience, while subjective support and marital status were found to be predictors of female survivors’ resilience. Annual household income and chronic disease were predictors for both male and female groups. The findings of this study can be used in devising methods to boost survivors’ resilience by promoting their satisfaction with social support and their ability to obtain effective support. Additionally, the results suggest how to assist survivors who may have relatively poor resilience.